The Biography of Lady Fatimah al-Zahra (peace be upon her) in the Book “Tadhkirat al-Khawas” by Sibṭ ibn al-Jawzi (d. 654 AH / 1256 AD) - Uda, Du’aa Jabbar (Thi Qar Arts Journal, 2024)
This research discusses the biography of the pure lady Fatimah al-Zahra (peace be upon her) through the book “Tadhkirat al-Khawas min al-Ummah bi Dhikr Khasa’is al-A’immah” by its author Sibṭ ibn al-Jawzi. The study briefly touches upon the life of the author, then delves into the birth of Lady Fatimah (peace be upon her), her names, titles, blessed marriage, pure offspring, inheritance, virtues, illness, and death. The research includes the text of the narrations, their documentation from other sources, and their authenticity. It also examines whether the author’s adherence to the Hanafi school of thought influenced his transmission of narrations that honor her. Additionally, it addresses the narrations that Sibṭ ibn al-Jawzi omitted.